2002
DOI: 10.1128/iai.70.9.4925-4935.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Mapping of theMycoplasma fermentansP29 Adhesin

Abstract: Initial adherence interactions between mycoplasmas and mammalian cells are important for host colonization and may contribute to subsequent pathogenic processes. Despite significant progress toward understanding the role of specialized, complex tip structures in the adherence of some mycoplasmas, particularly those that infect humans, less is known about adhesins through which other mycoplasmas of this host bind to diverse cell types, even though simpler surface components are likely to be involved. We show by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Indeed, peptide 7 of P1 was found to bind a specific host receptor that was shared with the P1 protein, suggesting that the inhibiting peptides function through the blockage of specific host cell receptors. Similarly, a fragment of the P29 adhesin from Mycoplasma fermentans inhibits the adhesion of the bacteria to HeLa cells through the blockage of host cell receptors (Leigh & Wise, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, peptide 7 of P1 was found to bind a specific host receptor that was shared with the P1 protein, suggesting that the inhibiting peptides function through the blockage of specific host cell receptors. Similarly, a fragment of the P29 adhesin from Mycoplasma fermentans inhibits the adhesion of the bacteria to HeLa cells through the blockage of host cell receptors (Leigh & Wise, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…(CDSs MFE_07470, MFE_07870 and MFE_01840) are associated with ABC transporters. Furthermore, earlier studies have shown that a 48 kDa lipoprotein (MFE_ 07870) of M. fermentans is associated with the ability of this organism to modulate the host immune system (Hall et al, 1996;Mühlradt & Schade, 1991), and a 29 kDa lipoprotein (MFE_00220) is the major adhesin of this organism, playing a role in the adhesion of the mycoplasma to eukaryotic host cells (Leigh & Wise, 2002;Theiss et al, 1996). In addition to lipoproteins, 119 membranespanning proteins were predicted, 12 of them possessing six transmembrane domains.…”
Section: Membrane-associated Proteinsmentioning
confidence: 99%
“…This also provided verification of the number of repeats in the recombinant vmcF sequence. Fusion protein was overexpressed from each recombinant construct and purified by amylose affinity chromatography as described previously (25).…”
Section: Methodsmentioning
confidence: 99%
“…Although the actual structure of these proteins has yet to be assessed experimentally, their lack of predicted structure could reflect one of several key biological roles for intrinsically unstructured proteins (12). An additional, opportunistic role can be imagined for Vmc proteins, based on the demonstration that phase-variable adhesion-associated lipoproteins containing repeated, often coiled-coil regions occur in diverse mycoplasma species (2,25,51,63,64), although any such role in M. capricolum subsp. capricolum is entirely speculative.…”
Section: Vol 188 2006 Phase-variable Genes In Mycoplasma Capricolummentioning
confidence: 99%